Habitat monitoring and genotoxicity in Ucides cordatus (Crustacea: Ucididae), as tools to manage a mangrove reserve in southeastern Brazil - Pinheiro, M. A A [UNESP]; Duarte, L. F A [UNESP]; Toledo, T. R. [UNESP]; Adam, M. L.; Torres, R. A. (Springer Nature, 2013)
In Brazil, the state of São Paulo contains both preserved areas (Juréia-Itatins Ecological Station) and extremely impacted ones (Cubatão Municipality). This study evaluated the concentrations of five metals (Cu, Cd, Cr, Pb, and Hg) in two mangroves with different levels of anthropogenic impact and the apparent genotoxicity to Ucides cordatus. Water and sediment samples were obtained, and metal concentrations were determined with an atomic absorption spectrophotometer. The genotoxic impact was quantified based on the number of micronucleated cells per 1,000 analyzed (MN‰), using hemolymph slides stained with Giemsa. Metal concentrations in water were below the detection limit, except for lead, although no significant difference was observed between the areas (P > 0.05). Sediment from Cubatão had higher concentrations of Cd, Pb, Cr, and Cu than sediment from Juréia-Itatins (P < 0.05), but no significant differences in metal concentrations were detected among depth strata of the sediment (P > 0.05). Crabs from Cubatão had a 2.6 times higher mean frequency of micronucleated cells (5.2 ± 1.8 MN‰) than those from Juréia-Itatins (2.0 ± 1.0 MN‰; P < 0.0001). The more-polluted conditions found in the mangrove sediments of Cubatão were reflected in the micronucleus assay, demonstrating their genotoxic effect; however, genetic damage should be attributed to a synergistic effect with other kinds of pollutants previously recorded in different environments of Cubatão. U. cordatus proved to be an excellent bioindicator of mangrove pollution. This study established, for the first time, the normal frequency of MN‰ in a population of this species within an ecological station. © 2013 Springer Science+Business Media Dordrecht.
Keywords: Contamination; Ecological station; Estuary; Mangrove; Metal; Micronucleus